“Principales daños ocasionados por la gomosis (Phytophthora citrophthora) en el cultivo de mandarina (Citrus reticulata). - Vergara Benavides, Marcos Veraldo (2024)
The document compiles information on the main damages caused by gummosis (Phytophthora citrophthora) in the mandarin crop (Citrus reticulata). The objectives set were to describe the damage caused by gummosis in the mandarin crop and detail the alternatives that will allow better control of gummosis in the mandarin crop, developing through the compilation of a wide range of information collected through research on various websites, scientific articles and bibliographic sources available on digital platforms. The conclusions determined that one of the most notable symptoms is the production of gummy substances, particularly observed in the trunk and main branches of the plantation. Some that can be implemented to prevent the development of Gummosis in citrus trees include taking precautions during injecting to avoid causing wounds and injuries, removing infected areas as soon as the disease arises, ensuring optimal humidity levels to discourage the growth of fungi, apply recommended fungicides and products particularly on the trunk, respecting the appropriate planting depths and carrying out periodic inspections to detect early signs of the disease and administer fungicides to the trunk, at intervals of two to three times a year. It is possible to improve the quality of the plaster by applying copper sulfate.